Lets mediate a teachers' guide to peer support and conflict resolution skills for all ages - Stacey, Hilary; Robinson, Pat.; Sage eBooks (Clifton : Lucky Duck, 1997)
In a world that fails to manage conflict, those who seek peaceful resolution are urged to promote mediation as a positive solution. Topics covered include: circle time, emotional literacy, affirmation, problem solving, co-operation, conflict resolution, communication, mediation.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mediation; Peer counseling of students; Electronic books